PENAMBAHAN KARAGENAN PADA PEMBUATAN SIRUP DARI BONGGOL NANAS - Fajri, Annur; Herawati, Netti; Yusmarini, Yusmarini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research was to determine the addition effect of carrageenan and get the best concentration of carrageenan on the quality of pineapple hump syrup produced. This research used Completely Randomized Design by five treatments and three replications. The treatments were K0 (without addition of carrageenan), K1 (addition of carrageenan 0.50%), K2 (addition of carrageenan 0.75%), K3 (addition of carrageenan 1.00%), and K4 (addition of carrageenan 1.25%). The obtained data were analyzed by Analysis of Variance followed by Duncan's New Multiple Range Test at 5% level. The results of variance showed that the addition of carrageenan at differential concentrations significantly affected the sucrose content, pH, viscosity, colour, taste, and consistency, but did not significantly effect the flavour and overall hedonic ratings pineapple hump syrup produced. The best treatment of the parameters tested and complied SNI 01-3544-2013 was the treatment K3 whith the addition 1.00% carrageenan. The treatment K3 contained sucrose content of 74.29%, pH of 4.95, viscosity 395.39cP, with a description of the colour was yellow, scented pineapple, sweet taste, which had cosistency viscous, and overall rated were liked by the panelists with a score 4.25. Keywords: Syrup, pineapple hump, carrageenan